RESOLUSI KONFLIK LAHAN DI DESA BEKALAR KECAMATAN KANDIS KABUPATEN SIAK - Kristiani Larosa; Harapan Tua (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Land is a very basic human need, this is because all activities and human life, both directly and indirectly, cannot be separated from land. In addition, land also has economic, social, political and cultural functions in human life. These conditions make land a permanent asset and have economic value for sustainable life, coupled with the increasing population so that the need for land is also increasing. Thus, this is what often causes conflict. One of the conflicts in Siak Regency occurred in Bekalar Village, Kandis District. This conflict occurred between PT. Arara Abadi with Bekalar Village Farmers, where the conflict occurred because the Bekalar Village Farmers' oil palm plantations were in a forest area which was a company concession. This study aims to find conflict resolution caused by the conflict that occurred. This study uses qualitative research through a descriptive approach and the necessary data, both primary and secondary data, are obtained through observation, interviews and documentation and then analyzed based on the research problem. In this study the theory used is conflict resolution theory by Fisher (in Fina, 2017), namely Negotiation, Mediation and Arbitration. The results of the study show that this case has not found a bright spot in resolving the conflict between the two parties, thus a conflict resolution is needed to provide justice and fulfill the rights of the Bekalar Village Farmers, Kandis District. This form of intervention must have a positive impact on both conflicting parties in order to create a peaceful social life. Keywords: Conflict, Conflict resolution, Land Conflict